The Relationship Between Social Influence and ICT Adoption among Senior Citizens - Binti Mohd Azali, Mariah; A. Gani, Norhaninah (Jurnal Evolusi, 2020)
The use of information and communication technology (ICT) by senior citizens is becoming an increasingly important and complex societal issue. As the world’s population ages, there is a greater need to comprehend the factors that influence older people’s adoption of ICT and the implications for their quality of life, social connectedness, and overall well-being. This study delves into the various aspects of ICT adoption among senior citizens, such as the barriers, motivators, and impact on their lives. To obtain insights from an array of senior citizens, the study employs a quantitative method approach that includes questionnaires and administered by 158 people at Apartment Harmoni, Petaling Jaya. Understanding ICT adoption has benefited greatly from studies, especially when viewed through the Unified Theory of Acceptance and Use of Technology.